THE MENSTRUAL HYGIENE MANAGEMENT PRACTICES AMONG SECONDARY SCHOOL GIRLS OF LIRA SUB-COUNTY LIRA CITY WEST. A CROSS-SECTIONAL STUDY. - Nakaweesi , Margret (Student’s Journal of Health Research Africa, 2023)
Background: Menstrual hygiene management (MHM) remains a public health concern globally, and menstruating girls in school environments face several challenges which include a lack of adequate, clean, safe, private toilets with water and disposal mechanisms for used menstrual materials, a lack of information, guidance, and support on their changing bodies and insufficient materials for managing monthly menstrual flow. Despite the initiative of several organizations to create awareness and highlight the importance of good MHM, the actual proposed actions to address MHM are still largely underdeveloped Aim: This study aimed at assessing the MHM practices among secondary school girls in the Lira Sub-County Lira City West division. Method: A cross-sectional study employing quantitative techniques was done. Data was collected from 312 participants by the use of semi-structured questionnaires. Data entry and analysis were done using SPSS version 23. Result: Poor menstrual hygiene management practice was 61.5%, and the age of respondents (P-value 0.000), mother’s education level (P-value 0.011), and father’s occupation (P-value 0.011), were significantly associated with MHM practices with a P value <0.05. Conclusion: Almost two-thirds (61.5%) of the students had poor MHM practices. Although there are some cases of sanitary pad usage, still MHM practices are unhygienic indicating that water, sanitation, and hygiene facilities in the schools need urgent solutions.